대학수학능력시험 한국지리 과목의 위치정보 문항 출제 경향 연구: 인문(경제)지리 문항을 중심으로 - 이소영; Soyoung Lee (한국경제지리학회지, 2021)
위치 지식은 지리학에서의 핵심개념이자 고차적인 지리적 사고를 위한 기초개념이다. 그럼에도 불구하고, 학생들의 위치 지식은 우리나라를 포함하여 전 세계적으로 약화되는 추세에 있다. 이러한 문제의식의 일환으로 본 연구에서는 대학수학능력시험 한국지리과목의 위치정보 문항 분석을 통해 출제의 경향성 및 학생들의 위치 지식 수준을 진단하고자 한다. 연구 결과는 다음과 같다. 첫째, 평가 요소로서의 출제 지역이 공간적으로 편중되어 나타났고, 특히 영남권에서 가장 많이 출제되었다. 둘째, 사실 기반 위치정보 문항에서는 지역특산물과 같은 지리적 표시제, 지역축제 등 지역성을 묻는 내용이 많았다. 셋째, 개념 기반 위치정보 문항의 내용은 자연지리와 인문지리영역으로 구성되는데, 경제지리와 관련된 문항은 농업 2건, 공업 2건으로 총 4문항이 출제되었다. 넷째, 학생들은 위치정보 문항을 어렵게 느끼는 경향이 있었다. 유형에 따라 어려움의 정도는 상이했는데, 학생들은 고차적 사고를 요하는 개념 기반 문항을 더 어렵게 느꼈다. 그중 경제지리 관련 문항을 두 번째로 어려워하는 것으로 나타났다. 마지막으로 출제 지역의 스케일에 따라서도 정답률의 차이가 있었는데, 학생들은 보다 정밀한 스케일에서의 문항을 상대적으로 더 어렵게 느끼는 것으로 나타났다. The present research explores the tendency of the items that require Place Location Knowledge (PLK) of the Korean Geography subject in the College Scholastic Ability Test. The major findings are as follows. First, the geographical regions of the items are spatially skewed, especially in the Yeongnam regions, which are tested more frequently compared to the others. Second, the fact-based items more concern with regionality such as geographic indication system and regional festivals. Third, the concept-based items can be divided into physical geography and human geography and there were four items related to economic geography. Fourth, students tend to find it challenging in the items asking PLK. The difficulty varies according to the type of items. The students find concept-based items which require high-order thinking more challenging. There is also differences identified between contents. For example, the section of physical geography, especially climatology-related, were considered the most challenging followed by those of economic geography. Finally, the differences in the rate of correct answer are associated with the scale of the regions covered in the items and students experienced more difficulty in the items asking more precise scale.